2023
DOI: 10.1021/acsami.2c22780
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone–MXene Nanofibrous Scaffolds for Tissue Engineering

Abstract: New conductive materials for tissue engineering are needed for the development of regenerative strategies for nervous, muscular, and heart tissues. Polycaprolactone (PCL) is used to obtain biocompatible and biodegradable nanofiber scaffolds by electrospinning. MXenes, a large class of biocompatible 2D nanomaterials, can make polymer scaffolds conductive and hydrophilic. However, an understanding of how their physical properties affect potential biomedical applications is still lacking. We immobilized Ti 3 C 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Ti 3 C 2 T x MXene nanosheets is a two-dimensional (2D) material with superior electrical conductivity (>10 5 S m –1 ) and high biocompatibility. Ti 3 C 2 T x MXene nanosheets were synthesized by etching Ti 3 AlC 2 MAX crystals in a solution of hydrochloride acid (HCl) and lithium fluoride (LiF) followed by exfoliation (see the Experimental Section). The SEM images of the MAX crystals are shown in the inset of Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…Ti 3 C 2 T x MXene nanosheets is a two-dimensional (2D) material with superior electrical conductivity (>10 5 S m –1 ) and high biocompatibility. Ti 3 C 2 T x MXene nanosheets were synthesized by etching Ti 3 AlC 2 MAX crystals in a solution of hydrochloride acid (HCl) and lithium fluoride (LiF) followed by exfoliation (see the Experimental Section). The SEM images of the MAX crystals are shown in the inset of Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…The employment of biocompatible dopants may also lead to the incorporation of the maximum allowable dopant concentrations, present within the structure that makes it a desirable candidate for biomedical engineering approaches [24]. As shown in figure 5(a), pure PCL mats showed no significant difference in H9c2 cell viability for all time points in comparison to the control group as PCL is a biocompatible polymer with desirable physicochemical properties [79]. Therefore, it can be a desired candidate to be recruited as the template or carrier for the in-situ polymerization of PANI and investigation of PANI biocompatibility.…”
Section: In Vitro Cell Studies 331 Biocompatibility Assessment Of Car...mentioning
confidence: 99%
“…It has been reported that double or triple layers of MXene deposited on the target substrate can form an appropriate environment for cell attachment and proliferation with a mild antibacterial effect. [158] Additionally, nanomaterial-assisted photothermal stimulation has been demonstrated to precisely modulate cellular activity with high spatiotemporal resolution, so as to better understand the electrical communications in both health and disease. Wang et al [159] demonstrated that Ti 3 C 2 T x MXene resulted in local temperature rises of 2.31±0.03 K and 3.30±0.02 K for 635 and 808 nm laser pulses respectively, implying outstanding photothermal response (Figure 7C).…”
Section: Emerging 2d Materials (Especially Mxenes)mentioning
confidence: 99%